1989
DOI: 10.1128/aac.33.5.612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fleroxacin (RO 23-6240) as single-oral-dose therapy of culture-proven chancroid in Nairobi, Kenya

Abstract: Chancroid is gaining importance as a sexually transmitted disease because of its association with transmission of human immunodeficiency virus type 1 (HIV-1). Effective, simply administered therapy for chancroid is necessary. Fleroxacin is effective against Haemophilus ducreyi in vitro. We performed an initial randomized clinical trial to assess the efficacy of fleroxacin for treatment of chancroid in Nairobi, Kenya. Fifty-three men with culture-positive chancroid were randomly assigned to receive either 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Animal studies have suggested that there is excellent penetration of drug into most tissues (5, 18, 30-34, 41, 49, 53), but only limited information on tissue penetration of fleroxacin in humans is available (22,26,41,44,53). Initial clinical experience in the treatment of sexually transmitted diseases, urinary tract infection, skin and soft tissue infections, gastrointestinal infection, and even acute exacerbations of chronic bronchitis has been quite promising, with 74 to 100% bacteriological cure rates and a tolerability comparable to those for other drugs of this class (3,12,27,35,38,42,43,45,47). However, to optimize the clinical use of * Corresponding author.…”
mentioning
confidence: 99%
“…Animal studies have suggested that there is excellent penetration of drug into most tissues (5, 18, 30-34, 41, 49, 53), but only limited information on tissue penetration of fleroxacin in humans is available (22,26,41,44,53). Initial clinical experience in the treatment of sexually transmitted diseases, urinary tract infection, skin and soft tissue infections, gastrointestinal infection, and even acute exacerbations of chronic bronchitis has been quite promising, with 74 to 100% bacteriological cure rates and a tolerability comparable to those for other drugs of this class (3,12,27,35,38,42,43,45,47). However, to optimize the clinical use of * Corresponding author.…”
mentioning
confidence: 99%
“…The quinolones rosoxacin, ciprofloxacin, enoxacin, norfloxacin, and fleroxacin have all proved to be effective in the treatment of chancroid (1,3,4,15,23,25,26). Although some of these agents have been found to be effective following single-dose administration, the efficacy of such (23).…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…Although some of these agents have been found to be effective following single-dose administration, the efficacy of such (23). Sulfonamide-trimethoprim combinations have also become established as one of the treatments of choice for the disease in many areas.…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…Centers for Disease Control and Prevention (CDC) recommend azithromycin, ceftriaxone and erythromycin for the treatment of chancroid [16]. However, single-dose treatment by these drugs was found not to be successful in more than 20% of chancroid therapies [17][18][19]. Furthermore de novo mutations and horizontal gene transfer mechanism in H. ducreyi may lead to development of drug resistance genes [17,20].…”
Section: Introductionmentioning
confidence: 99%